Distances from the root apices of posterior teeth to the maxillary sinus and mandibular canal in patients with skeletal open bite: A cone-beam computed tomography study - Werinpimol Kosumarl (2018)
© 2017 by Korean Academy of Oral and Maxillofacial Radiology. Purpose: This study determined and compared the distances from the maxillary root apices of posterior teeth to the floor of the maxillary sinus, or maxillary sinus distances (MSDs), and the distances from the mandibular root apices of the posterior teeth to the mandibular canal, or mandibular canal distances (MCDs), in Thai subjects with skeletal open bite and skeletal normal bite. Materials and Methods: Pretreatment cone-beam computed tomography (CBCT) images were obtained from 30 Thai orthodontic patients (15 patients with skeletal normal bite and 15 with skeletal open bite) whose ages ranged from 14 to 28 years. The CBCT images of the patients were processed and measured using the Romexis Viewer program. The MSDs and MCDs from the root apices of the maxillary and mandibular second premolar, first molar, and second molar to the maxillary sinus floor or the mandibular canal were measured perpendicularly to the occlusal plane. The Student t test was used for comparisons between the 2 groups. Results: The greatest mean MSDs were from the root apex of the second premolars in both groups, whereas the least mean MSDs were from the mesiobuccal root apex of the second molars. The greatest mean MCDs were from the mesial root apex of the first molars, whereas the least mean MCDs were from the distal root apex of the second molars. Conclusion: There were no differences in the mean MSDs or the mean MCDs between the skeletal normal bite group and the skeletal open bite group.